Customer Satisfaction towards Telecommunication mobile services: A case study in Asiacell Telecommunications in Sulaymaniyah city - Mohammed, Blesa Ibrahim; Andavar, Venkatesh (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
Asiacell a leading provider of telecommunication in all the regions of Iraq is established in Sulaymaniyah city of Kurdistan region. With over 14 million customers this company is very popular among the prepaid mobile customers. The purpose of this study is to identify the satisfaction of customers using the prepaid services of Asiacell. So an administered questionnaire was used to collect responses from 1740 randomly selected customers in different location of Sulaymaniyah city for this study. The responses were analysed using descriptive method as the responses were so direct and precise. From the observed results of the study it is found that majority of the users of Asiacell were young customers and vast majority of them were satisfied with the prepaid mobile services provided by the Asiacell company in the city of Sulaymaniyah. But it is also to be noted that the customers’ expectation on some of the service areas like pricing and customer query responses are in need of revision by the Asiacell company based on the expectations of the customers.